Conflict count between school children and motorized traffic around traffic-calmed school areas - Poi, Alvin Wai Hoong (2010)
In Malaysia, police statistics data reveals that the number of child pedestrian casualties in the vicinity of schools showed a decreasing trend from 1995 up to year 2004. Despite the decrease trend, more efforts should be put to further reduce the number of school children casualties. One of the ways is through appropriate engineering interventions that modify the built environment around school areas to promote safe travel to and from schools. The built environment around schools in Malaysia varies from school to school which offers different ways of protection to school children on the road. As such, the effects of the different built environment to the safety of school children need to be examined in order for appropriate treatment to be identified. This study adopted the use of traffic conflict technique to examine the effects of different built environment in the vicinity of schools. The main objective of this study was to examine the effects of various built environment on the rate of conflict between school children and vehicular traffic at traffic calmed schools. In order to achieve the main objective, statistical models were developed and the traffic flows criteria for the provision of interventions were established. A total of 50 study sites in Serdang, Seri Kembangan, Kajang, Bangi and Cheras were included in this study. The generalized linear modeling with Poisson distribution was used to develop the models. The final models revealed that vehicle-pedestrian flows, road width, presence of sidewalks and traffic wardens were significant in explaining the conflict counts. Other built environment variables such as vehicle approaching speed, presence of zebra crossing and types of land use were not significant. Presence of traffic warden had the highest effect on the variation of conflict counts. The models developed in this study can be used to predict the expected number of conflict counts per hour happening near the entrance of schools. The traffic flows criteria established from the models can be used as a guide on the implementation of appropriate interventions in the vicinity of schools.